Tindakan Sosial Masyarakat Dalam Pengelolaan Sampah di Kota Padang - Laveni, Betti; Genta Firanda Putra; Arib Arsalan; Mohammad Geunta; Syamsir Syamsir (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2023)
Lack of public understanding of the importance of waste management is a major consideration in overcoming waste problems. Not only relying on government mediation and depending on cleaning staff Of course, but the local area as the main producer of waste must accept activity in administration. The essence of this exploration is: 1) knowing the basis behind the existence of waste management in the city of Padang, 2) knowing the structure of waste management in the city of Padang, 3) knowing the social activities of the local city community in managing waste. This study uses a qualitative subjective exploration strategy. Methods The variety of information used are: perceptions, meetings, and documentation. The information legitimacy test is carried out through source triangulation. The procedure for investigating information in this study uses the stages of data collection, data reduction, data presentation, and drawing conclusions. The hypothesis used is the Social Action Hypothesis. The results of this study are social activities carried out by Padang residents in conquering the waste problem confirmed by the arrangement of various types of waste management, such as TPS 3R, Garbage Bank, and Garbage Scholarship.